Cobertura do solo, produção de biomassa e teores de mn e zn de alface no sistema orgânico - Mógor, Átila Francisco; Câmara, Francisco Luiz Araújo [UNESP] (Universidade Estadual de Maringa, 2009)
The goal of this research was to evaluate the effect of soil covering with black oat straw, as well as soil covered with black plastic, on the production of biomass and levels of Mn and Zn in lettuce produced in an organic system, over two consecutive years. Five treatments were used: soil without cover, covered with black plastic, covered with laying oats, covered with harvested oats, and covered with oat straw in natural form, for growing three cultivars of lettuce. A randomized blocks design was used in a splitplot system, with four replications. It was concluded that soil covered with oat straw promoted satisfactory lettuce production, as well as adequate Mn and Zn content in plants, equivalent to those found in studies conducted under different growing systems; the soil covered with black plastic promoted satisfactory production and higher Zn content after the first year, and lower Mn content after the second year.
Soil covering, biomass production, and Mn and Zn content of lettuce in organic system
Keywords: Avena strigosa; Covered soil; Lactuca sativa L.; Manganese; Organic production; Zinc